L’impact environnemental de la construction des prisons : l’exemple de l’artificialisation des sols - Mélanie Bouteille; Lucie Bony (Territoire en Mouvement)
Since 2016, around thirty prisons have been planned on French territory, mainly on large areas of non-artificial or agricultural land. This vast real estate program thus comes into contradiction with the objectives of land sobriety included in urban planning documents since the solidarity and urban renovation law (SRU) of 2000 and reinforced since the establishment in 2021 of the zero net artificial land use (ZAN) in the Climate and Resilience Act. The challenge of this article is to understand how this regulatory evolution influences the construction of contemporary prisons. Based on the analysis of cartographic and statistical data, the study of gray literature and the conduct of interviews, this article analyzes in a first part the effects of the construction of penal establishments on urban sprawl and assesses the extent of land artificialization caused by prisons. The second part of the article is devoted to the study of the strategies implemented by prison designers to limit the effects on the artificialization of the territory by following the sequence “avoid, reduce, compensate” (ERC).